(untitled) (Fiep Bulletin - online, 2012)
The objective of this study was to present the profile of elderly residents in long-term institutions. This is an epidemiological descriptive study conducted in long-term institutions (ILP) in João Pessoa - Paraíba, Brasil, with seventy people in the age between 60 and 98 years, of both sexes who answered a semi structured interview. The data were transferred to SPSS, a statistical analysis on by the construction of simple frequency tables, descriptive measures, cross-variables. The results point to the health status of 58.6% did not report any illness; however, 41.4% of the elderly report at least one type of disease. The most frequently mentioned diseases were arterial hypertension, diabetes mellitus.